PELATIHAN TROUBLESHOOTING KEAMANAN JARINGAN PADA JARINGAN WAN PADA SMK SULTAN SYARIF QASIM KANDIS - Zulafwan Zulafwan; Syarfi Aziz; Willyansah Willyansah; Syahrul Syahrul; Nanang Kurnia Wahab; Budi Ariadi (LPPM Universitas Bina Bangsa, 2023)
This community service activity is one part of the Tri Dharma of higher education which. Must be carried out by a lecturer. This service is carried out as a form of knowledge transfer to the community in the role and responsibility of intelectuals in preserving and chaining cultural treasure. Based on the results of the activities and disscution that there is a significant increase in knowledge and expertise in security troubleshooting on WAN networks. To achieve maximum results, a joint effort is needed between teachers and students, so that stabilization is needed for students with various problem models